Cost-efficient, true silicone printer with variable material spectrum for individualized medical applications - Martin, Sina; Gugel, Lukas; Martin, Thomas; Preis, Alexander; Reitelshöfer, Sebastian; Franke, Jörg (Procedia CIRP, 2021)
Due to their beneficial material properties, silicones have become increasingly important in the healthcare sector. However, common manufacturing techniques like injection molding are limited. Hence, silicones have become more interesting for additive manufacturing, as it is possible to freely shape individualized products in small quantities. We present a syringe printer architecture for personalized manufacturing of medical products that allows a variable mixing ratio for RTV-2 crosslinking silicones and precise dosing. Compared to other printing methods, various commercially available one or two-component silicones with variable part viscosities can be printed in a broad range from 10-3Pas up to 10³ Pas.
Keywords: Additive manufacturing; individualized healthcare; silicone printing; medical grade silicones

Pre-crosslinking Dependent Layer Adhesion in Additive Manufacturing of RTV-2 Silicone - Gugel, Lukas; Mashhouri, Sara; Franke, Jörg; Martin, Sina (Procedia CIRP, 2024)
Additive manufacturing (AM) with silicone rubbers gains increasing attention in research and industry, by enabling a mold free production of complex and soft parts for various use cases in e. g. medical technologies or mechanical engineering. Many silicone AM processes incorporate an extrusion-based layer by layer process of alternately printing liquid silicone rubber and crosslinking it subsequently. Lower layers therefore must support the weight of the upper layers and thus must be crosslinked to a sufficient degree before the next layer can be started. Moreover, fast and sufficient crosslinking is necessary to achieve fine part details and a high surface quality, especially for low viscosity silicone. However, the extrusion on pre-cured silicone rubber layers may have a negative effect on the interfacial layer adhesion and thus weaken the mechanical properties of the part. Here we show that the layer adhesion of RTV-2 (Wacker Elastosil® P7670) silicone linearly decreases relative to an increasing state of crosslinking of the base layer for the investigated time window of 35 to 125 min at room temperature. This adds more comparable knowledge to few scientific reports that were published using different silicones and testing strategies. The printing process has to be tuned according to the presented findings. It can therefore be necessary to print on less pre-crosslinked silicone layers to achieve a better layer adhesion and thus accept increased rubber spreading and a reduced geometric accuracy. While the specific material tested is used at FAPS institute for printing parts, it is to be expected that the results can be transferred to similar two component silicone system

Printed stretchable dielectric sensor grids for pressure monitoring in orthopedics - Martin, Sina; Gugel, Lukas; Schedel, Sophie; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
Scoliosis is a spinal deformity that can be treated with a scoliosis brace that applies pressure to the trunk. The child's body adapts to the applied pressure and the spine is corrected. However, the braces are adjusted periodically or after rapid growth without monitoring the adaptation process. This study proposes to investigate the pressure distribution in the internal padding of the brace in order to adapt the orthosis to the individual needs of the patient in the long term. For this purpose, the implementation of dielectric elastomer sensors is used to detect pressure peaks and valleys on a mutual capacitance sensing grid. Subsequently, direct ink writing is used to print electrode lines, allowing analysis of the flexible electrode grid geometries. The electrodes are characterized and tested under uniaxial strain. Furthermore, by placing the electrodes on the padding of the orthosis, the relative pressure distribution can be assessed. Our results demonstrate the application of dielectric elastomer sensors in orthopedics and explore the effect of different printed geometries. Although absolute values have not been evaluated, characterization of relative pressure differences is sufficient to detect pressure points. By monitoring long-term changes, therapy can be tailored to the body's individual adaptation process.
CRIS-Team Scopus Importer:2024-06-07
Keywords: additive manufacturing; Mutual capacitance; orthopedics; percolation; pressure sensor

Thermoelectric Printhead Cooler for a Stable Process and Curing Control in RTV-2 Silicone Additive Manufacturing by Direct Ink Writing - Gugel, Lukas; Martin, Sina; Preis, Alexander; Franke, Jörg (Procedia CIRP, 2023)
The direct additive manufacturing, such as Direct Ink Writing (DIW), of silicone parts holds cost and complexity advantages. However, for extruding strands of low viscosity heat curing silicone rubbers, a build plate temperature of up to 90°C is used, which comes with the challenge of early vulcanization inside the printhead. Thus, this paper presents a thermoelectric cooler for universal printheads. At a build plate temperature of 90°C it prolongates vulcanization by 198.5 % (∆tpot life = 508.8 s), which allows a reduction of print speed for higher quality. Additionally, the influence of external temperature is reduced and the viscosity can be controlled. <br
Keywords: Direct Ink Writing; Vulcanization; Silicone; Silicone rubber; Additive Manufacturing; Thermoelectric cooler; Viscosity